2022
DOI: 10.3390/e24070994
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Ecohydrological Model Sensitivity to Input Variability with an Information-Theory-Based Approach

Abstract: Ecohydrological models vary in their sensitivity to forcing data and use available information to different extents. We focus on the impact of forcing precision on ecohydrological model behavior particularly by quantizing, or binning, time-series forcing variables. We use rate-distortion theory to quantize time-series forcing variables to different precisions. We evaluate the effect of different combinations of quantized shortwave radiation, air temperature, vapor pressure deficit, and wind speed on simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…We also did not specifically focus on the optimization of hyperparameters within each ML model, which could have an effect on functional and predictive performance. Moreover, the precision and general quality of the forcing variables and Fc are important as they have underlying uncertainties and have been gap-filled, and our interpolation methods may have more effect on some model structures than others and future research could explore how models use information encoded in forcing data (Farahani et al, 2022). We also note that the MLR performance can be significantly influenced by multicollinearity among the forcing variables, and we did not test for this aspect.…”
Section: Discussionmentioning
confidence: 97%
“…We also did not specifically focus on the optimization of hyperparameters within each ML model, which could have an effect on functional and predictive performance. Moreover, the precision and general quality of the forcing variables and Fc are important as they have underlying uncertainties and have been gap-filled, and our interpolation methods may have more effect on some model structures than others and future research could explore how models use information encoded in forcing data (Farahani et al, 2022). We also note that the MLR performance can be significantly influenced by multicollinearity among the forcing variables, and we did not test for this aspect.…”
Section: Discussionmentioning
confidence: 97%
“…We also did not specifically focus on the optimization of hyperparameters within each ML model, which could affect functional and predictive performance. Furthermore, the precision and general quality of the forcing variables and Fc measurements are important as they have underlying uncertainties and have been gap‐filled, and our interpolation methods may influence some model structures than others and future research could explore how models use information encoded in forcing data (Farahani et al., 2022). We also note that the MLR performance can be significantly influenced by multicollinearity among the forcing variables (Farahani et al., 2023; Mojtaba et al., 2023), and we did not test for this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of time-series data has proven valuable in extracting meaningful events in smart manufacturing systems [3]. While time-series data can be found in various domains such as healthcare [4], climate [5], robotics [6], ecohydrology [7], stock markets [8], energy systems [9], etc., this paper focuses on the plastic processing industry as a case study within the manufacturing domain. A comprehensive review of time-series applications in manufacturing can be found in [10].…”
Section: Introductionmentioning
confidence: 99%